Copula-based joint probability model for multi-peak wave slamming forces on box girder bridges - Lixuan Fei; Qinghe Fang; Pengfei Liu; Guochen Zhao; Anxin Guo (Engineering Structures, 2026)

Slab break-off-induced crust–mantle interaction and Triassic adakitic magmatism in the northern North China Craton - Zeguang Chang; Guochen Dong; Weijun Xu; Hongbin Li; Zhixiong Zhao (Lithos, 2026)

Longitudinal soil arch evolution in cobble tunnels using shallow tunnelling method: Experimental and DEM insights - Yiwen Qin; Fengyin Liu; Jinxing Lai; Junling Qiu; Guochen Tang; Wencai Zhao (Tunnelling and Underground Space Technology, 2026)

Effects of surrounding rock fracture behavior on the mechanical response of segmental tunnels crossing strike-slip faults - Guochen Zhao; Zheng Yang; Jingzhou Zhu; Longjun Xu; Shibin Lin; Lili Xie (Soil Dynamics and Earthquake Engineering, 2026)

Constructed wetland substrate–mediated stereoselective transformation of metolachlor: Influence of redox conditions and microbial community dynamics - Liangjin Chen; Yucong Zheng; Mawuli Dzakpasu; Qian Yang; Guochen Liu; Liping Zhao; Tianfu Wu; Dongfu Zhang; Xiaochang Wang; Rong Chen (Environmental Research, 2026)

Origin of granitic pegmatites: Perspectives from elements and Li Hf isotopes, Chakabeishan, northern Tibetan Plateau - Wenli Sun; Zhidan Zhao; Xuanxue Mo; Guochen Dong; Xiaowei Li; Wanming Yuan; Tao Wang; Bingzhang Wang; Tong Pan; Jie Han; Yan Tang; Ningyuan Qi; et al. (Lithos, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

Smart UAV-assisted blueberry maturity monitoring with Mamba-based computer vision - Fan Zhao; Yinyin He; Jian Song; Jiaqi Wang; Dianhan Xi; Xinlei Shao; Qingyang Wu; Yongying Liu; Yijia Chen; Guochen Zhang; Chenyu Zhang; Yulun Chen; et al. (Precision Agriculture, 2025)
Purpose Precise segmentation of blueberry maturity is critical for optimizing harvestschedules and maintaining product quality. Traditional methods, which rely on manualinspection, are not only labor-intensive but also cost-inefficient. This study presents a novelframework that integrates deep learning-based super-resolution reconstruction (SRR) withsemantic segmentation to provide a fast and accurate solution for maturity assessment. Methods The SRR module enhances image resolution, enabling more detailed feature extraction.Semantic segmentation models—incorporating convolutional neural networks (CNNs),Transformer-based models, and the Mamba-based state space architecture—further improvesegmentation precision. Results Experimental results indicate that the MambaIR modelachieves a structural similarity index measure (SSIM) of 82.26% in SRR tasks, while the Mamba-based segmentation model attains a mean Intersection over Union (mIoU) of 83.15%. Conclusion By uniting SRR and semantic segmentation, our framework not only advances thetechnical accuracy of maturity detection but also holds strong potential for real-time, cost-effective deployment in precision agriculture systems, supporting intelligent decision-making at scale.

Seafloor debris detection using underwater images and deep learning-driven image restoration: A case study from Koh Tao, Thailand - Fan Zhao; Baoxi Huang; Jiaqi Wang; Xinlei Shao; Qingyang Wu; Dianhan Xi; Yongying Liu; Yijia Chen; Guochen Zhang; Zhiyan Ren; Jundong Chen; Katsunori Mizuno (Marine Pollution Bulletin, 2025)

Removal of mixed PhACs by combined UV/H2O2 and biologically activated carbon process: Toxicity assessment, transformation products and microbial community - Qingmiao Yu; Guochen Shen; Fuzheng Zhao; Yaxuan Fan; Hongpu Xue; Yi Bao; Hongqiang Ren; Jinju Geng (Journal of Environmental Management, 2025)

Jurassic–cretaceous exhumation history of the Northern Qaidam Basin and its implications for Northeastern Qinghai–Tibet plateau tectonism: evidences from zircon fission track thermochronology - Zirui Feng; Wanming Yuan; Zhidan Zhao; Guochen Dong; Xiaowei Li; Wenli Sun; Li Yang; Shujiong Hong; Mingming Zhao; Caixia Hu; Shiyu Li (International Geology Review, 2024)

Temporal trend and driving effect of demographic transitions on embedded carbon emissions of Chinese households - Shuo Wang; Wenjin Zhao; Xian’en Wang; Guochen Zheng (Environmental Science and Pollution Research, 2024)

Design and synthesis of low-potential and cycling-stable cobalt dicarboxylate bipyridine complexes for high-voltage aqueous organic redox flow batteries - Bin Liu; Wei Wei; Yu Wang; Manrong Song; Youke Chen; Honglin Chen; Liuping Chen; Qiuxia Dai; Shengxin Yao; Junhui Xu; Guochen Jia; Tianshou Zhao (Science Bulletin, 2024)

Probabilistic seismic capacity models for circular tunnels at different performance levels - Longjun Xu; Jingzhou Zhu; Guochen Zhao; Shuang Li (Computers and Geotechnics, 2024)

Mesozoic–Cenozoic cooling, exhumation and tectonic implications of Chaqiabeishan–Shaliuquan Li Be ore district in the northeastern Qinghai–Tibet Plateau - Zirui Feng; Wanming Yuan; Zhidan Zhao; Guochen Dong; Xiaowei Li; Wenli Sun; Li Yang; Shujiong Hong; Mingming Zhao; Caixia Hu; Shiyu Li (Tectonophysics, 2023)

Genetic-simulated annealing optimization for surface wave inversion of shear-wave velocity profiles of geotechnical sites - Shibin Lin; Jeramy C. Ashlock; Guochen Zhao; Qinghui Lai; Longjun Xu; Changhai Zhai (Computers and Geotechnics, 2023)

Benzo[b]fluoranthene (B[b]F) affects apoptosis, oxidative stress, mitochondrial membrane potential and expressions of blood-brain barrier markers in microvascular endothelial cells - Shanshan Zhao; Qixue Bao; Guochen Ma; Yuqin Yao; Linshen Xie; Jingyuan Xiong (Toxicology in Vitro, 2023)

An analytical method for the thermo-mechanics coupling study of thin-walled spherical shell structure - Xingji Zhu; Kainian Jiang; Qingchen Liu; Lin Tang; Longjun Xu; Guochen Zhao; Changqing Gong (European Journal of Environmental and Civil Engineering, 2022)

Influence of saturated zone depth and vegetation on the performance of vertical flow-constructed wetland with continuous feeding - Guochen Liu; Zonglian She; Mengchun Gao; Jiacheng Liang; Chunji Jin; Liang Guo; Yangguo Zhao (Environmental Science and Pollution Research, 2018)

First-order perturbation approximation for rock elastic moduli in transversely isotropic media - GuoChen Wu; XiaoLong Zhao; Jie Tang; ZeYuan Du (Science China Earth Sciences, 2017)

Consecutive combined response spectrum - Longjun Xu; Guochen Zhao; Qingyang Liu; Yujian Xie; Lili Xie (Earthquake Engineering and Engineering Vibration, 2014)

Mantle input to the crust in Southern Gangdese, Tibet, during the Cenozoic: Zircon Hf isotopic evidence - Xuanxue Mo; Guochen Dong; Zhidan Zhao; Dicheng Zhu; Su Zhou; Yaoling Niu (Journal of Earth Science, 2009)

Identification of SCAR markers linked to or, a gene inducing beta-carotene accumulation in Chinese cabbage - Fenglan Zhang; Guochen Wang; Mei Wang; Xiucun Liu; Xiuyun Zhao; Yangjun Yu; Deshuang Zhang; Shuancang Yu (Euphytica, 2008)